Dynamical localization of matter-wave solitons in managed barrier potentials - Abdullaev, Fatkhulla Kh.; Garnier, Josselin (American Physical Soc, 2007)
The bright matter-wave soliton propagation through a barrier with a rapidly oscillating position is investigated. The averaged-over rapid oscillations Gross-Pitaevskii equation is derived, where the effective potential has the form of a finite well. Dynamical trapping and quantum tunneling of the soliton in the effective finite well are investigated. The analytical predictions for the effective soliton dynamics is confirmed by numerical simulations of the full Gross-Pitaevskii equation.